Quality of life, mood and cognitive performance in older adults with cognitive impairment during the first wave of COVID 19 in Argentina. (December 2021) - Aragón, Irina; Flores, Ignacio; Dorman, Guido; Rojas, Galeno; Sanjurjo, Natalia Sierra; O'Neill, Santiago
Abstract: Background: In Argentina, government has established lock down on 19 March in order to decrease SARS‐COV 2 infection. These restrictions have remained effective for long time, with increase of anxiety depression and insomnia as shown in several studies. Older population was particularly at risk due to greater limitations to go out. Our objective was to evaluate the impact of confinement in quality of life, mood and cognitive performance of older adults with cognitive impairment. Method: Longitudinal descriptive‐observational study. Patients with cognitive impairment (CDR 0.5‐1) attending to virtual cognitive stimulation sessions have participated. Participants have completed by themselves Quality of Life in Alzheimer's Disease scale (QOL AD), Beck Depression Inventory (BDI‐II), Test your Memory (TYM) and an attention and executive battery created by our institution. Same assessments were done at the beginning of the lock down and 7 months later. SPSS program was used and means, standard deviations and paired‐samples t test were calculated. Result: 51 adults (43 women, mean age: 68.53 SD: 8.06, mean education: 14.33 SD: 2.63) were included. An increase in BDI ‐II score ( p = 0.049) and worse performance in one of the executive attention tests ( p = 0.012) were found. No significant differences in total score of QOL‐AD ( p = 0.090), TYM (p = 0.067), verbal fluency ( p = 0.323) or memory tests ( p = 0.098) were found. Reviewing sub items, differences in changes in sleep habits ( p = 0.021), decrease in the energy level ( p = 0.004), worse subjective record of memory capacity ( p = 0.028) and decrease in ability to do housework ( p = 0.007) were found. In those who lived alone a higher score in BDI ‐ II ( p = 0.030) and TYM ( p = 0.22) were found. Conclusion: This is the first longitudinal study that measures the impact of lockdown on quality of life and cognitive performance in older adults with cognitive impairment in Argentina. Lockdown and isolation have shown worsening of mood and some quality of life variables and decrease in attention. Finally, our results show an increase in depressive symptoms in those patients who lived alone.